Comparative study of different injection modes on combustion and particle emission of acetone-butanol-ethanol (ABE) and gasoline in a dual-injection SI engine. (1st December 2020) - Guo, Zezhou; Yu, Xiumin; Li, Guoliang; Sun, Yao; Zhao, Zhe; Li, Decheng
Highlights: ABE/gasoline dual-fuel dual-injection mode is proposed. GPI + ABEDI mode owns the highest torque and brake thermal efficiency. GPI + ABEDI owns the lowest gaseous and particle emissions among three modes. ABE/gasoline injection approaches strongly influence particle distribution. GPI + ABEDI is the best injection approach for ABE/gasoline dual-fuel engine. Abstract: With the depletion of fossil energy and the aggravation of environmental pollution, using ABE as an alternative fuel in engines has become a research hotspot. In this paper, we conducted an experiment on a dual-injection spark ignition (SI) engine to compare three injection modes of ABE port injection plus gasoline direct injection (A + G), gasoline port injection plus ABE direct injection (G + A) and gasoline port injection plus gasoline direct injection (G + G) at different λ, engine speed, load and ignition timing. The results show that the torque of G + A mode is the highest at different engine speed, load and λ. CA0-90 of G + A and A + G are basically the same and lower than that of G + G mode, and CoVIMEP of G + A mode is lowest at each ignition timing. Besides, the G + A mode owns the highest BTE and is 0.2%, 0.4%, 0.02%, 0.05 and 0.6% higher than that of G + G mode at λ = 0.9 to 1.3, respectively. For gaseous emissions, NOx and HC emissions of G + A mode are the lowest under all the conditions. G + A mode owns the lowest CO emissions at λ = 0.9, 1.0 and 1.1, and all the CO values are lower than 0.1 vol% at λ = 1.2 and 1.3. For particle emissions, the G + A mode shows extremely low emissions under different engine speed, load and λ. The particle number of G + A shows unimodal distribution while the particle number of G + G and A + G modes shows the bimodal distribution. Overall, gasoline port injection plus ABE direct injection is the best injection approach for ABE/gasoline dual-fuel engine.